Сhronological and topographic peculiarities of infrahyoid structures during embryonic period of human ontogenesis. - Tsyhykalo, O. V.; Popova, I. S.; Dutka-Svarychevska, T. D. (Морфологія / Morphologia / Morfologìâ, 2019)
Background. A scientific investigation on prenatal development of neck structures is one of the key areas in human morphology. Such topicality is due to high frequency of congenital malformations in newborns,traumatic pathologies in adults and complications of odontogenic diseases. New research data on the problem of infrahyoid structures development in early embryonic and late prefetal period will lead to creation of new surgical ways of treatment and diagnostic criteria for various neck pathologies. Objective. Our study is aimed to examine sources, chronologic sequences and developmentalpeculiarities of infrahyoid structures in anterior neck region during early human ontogenesis. Methods. We have used specimens of human embryos and prefetuses, obtained from Chernovtsy Regional Pathologists Office. The research was conducted by the means of complex morphological methods: macro-and microscopy, three-dimensional reconstruction of histological slides and statistical analysis. Results. We have observed first germ of infrahyoid group of muscles in 6-week human fetuses(13,0 mm of parieto-coccygeal length (PCL)) which is visible as a large plate of fused muscle tissue. This tissue during next two weeks of development undergoes process of separation on smaller independent structures. In human prefetuses (14,0-20,0 mm of PCL)this presumptive tissue has signs of striation and nerve supply. The 9th week of PND is considered to be a finish point for separation process (prefetuses of 31,0 mm of PCL). Larynx cartilages are clearly visible in prefetuses of 31,0-32,0 mm of PCL. During middle prefetal period (8-9th month of PND) most of infrahyoid muscles, blood vessels and nerves follow closely the adult pattern. Conclusions. We have seenfirst signs of infrahyoid muscles precursors in 6-week human embryos, which can be considered as a first critical period in infrahyoid structures’ development. Separation of a common infrahyoid muscles germ is completed by the 9th week of middle prefetal period. The sternocleidomastoid muscle is developing from a common germ with that of trapezoid muscle. The 8th week of prenatal development can be considered as second critical period for possible congenital malformations development.